The effect of self-leadership in enhancing job dedication A survey of the opinions of a sample of medical and nursing staff at Imam Zain Al-Abidin Hospital in the holy Karbala Governorate - فرح سعدون عبد; حسين حريجة الحسناوي (Iraqi Journal for Administrative Sciences, 2024)
The research aims to test the relationship and effect of self-leadership in enhancing job dedication by analyzing the relationship between the dimensions of each of them. The research also began with a major problem, including the scarcity of writings on job dedication and self-leadership, especially with regard to the lack of Arabic writings. The research included several questions revolving around the nature of the relationship. Among its variables, the research relied on a purposive sample of individuals, which was represented by medical and nursing staff working at Imam Zain al-Abidin Hospital in the Holy Governorate of Karbala, and the number of individuals responding reached (200) individuals. The conclusions of the analysis of the two research variables also showed that there was a good convergence in the research sample’s responses to the dimensions of the two variables. The agreement of the response to the field sample indicates these dimensions.